(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The aim of this paper is the description, from both the biostratigraphical and sedimen• tological point of view, Of the lower member of the Rosso Ammonitico Veronese, one of the most known red, nodular, pelagic limestones of the mediterranean Jurassic. The R.A.V. is a condensed sequence Of red, mostly nodular, limestones, Often rich in internal molds Of ammonites, which is areally restricted to the "Trento Ridge", a structural high isolated in the early Jurassic by the rifting Of a Triassic, large epicontinental carbonate—platform. It spans in age from late Bajocian to Tithonian and is separated from the underlying shallow—water carbonates Of Liassic and Aalenian age by a sharp break in sedimentation, underlined by a mineralized hard ground, which lasted for all early and middle Bajocian. Two members may bc recognized in the R.A.V.: a lower (Rosso Ammonitico Inferiore) and an upper one (Rosso Ammonitico Superiore) separated by a stratigraphic gap. The lower member, ranging in age from late Bajocian to middle Callovian, is well developed only in the southern part of the ’Trento Ridge" (i. e. in the Lessini Veronesi area) and has a variable thickness which reaches a maximum of 8 meters.